2023
DOI: 10.3390/jpm13071125
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality Aspects in Post-COVID-19 Patients

Ioana Munteanu,
Monica Marc,
Constantin Gheorghevici
et al.

Abstract: In this observational cohort study, sleep quality in post-COVID-19 patients was assessed using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. This study aimed to examine aspects of sleep quality in patients who have undergone SARS-CoV-2 infection and if there is a pattern of progression or regression over time (6 months). We also observed and analyzed the results in order to identify any possible links between the severity of COVID-19 and sleep quality as measured by the PSQI questionnaire. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…GP’s observations of symptoms are broadly consistent with the current literature 2225 . Despite their high prevalence in epidemiological studies 2628 , sleep disturbances were rarely mentioned in the interviews, indicating a potential gap for targeted interventions. Furthermore, gastrointestinal problems, more common in post-COVID patients than in the general population 29 , were not explicitly addressed.…”
Section: Discussionmentioning
confidence: 99%
“…GP’s observations of symptoms are broadly consistent with the current literature 2225 . Despite their high prevalence in epidemiological studies 2628 , sleep disturbances were rarely mentioned in the interviews, indicating a potential gap for targeted interventions. Furthermore, gastrointestinal problems, more common in post-COVID patients than in the general population 29 , were not explicitly addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study evaluating sleep quality during the first six months after recovery from COVID-19 infection, Kalamara et al 26 reported persistent poor sleep quality at 1, 3, and 6 months. In a study in Romania, Munteanu et al 11 found an increased incidence of sleep quality problems at 6 months after recovery from COVID-19, with a higher rate in the mild-to-moderate groups. Jackson et al 12 reported that poor sleep quality persisted in cases after 2 to 14 months of recovery from COVID-19.…”
Section: Alterations Of Sleep Quality and Its Associations With Pulmo...mentioning
confidence: 97%
“…The PSQI was used to assess sleep quality in this study. The reliability and validity of the scale have been previously demonstrated for Vietnamese population 21 and it has been used in various countries to evaluate patients after recovery from COVID-19 infection [10][11][12] . The scale comprises 19 questions and evaluates sleep quality across seven components, including subjective sleep quality, sleep latency, sleep duration (h), sleep efficiency (hours slept/hours in bed), sleep disturbances, use of sleep medication, and daytime dysfunction 22,23 .…”
Section: Sleep Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 It also plays a crucial regulatory role in the immune system. 10 Given the reciprocal association between sleep and the immune system, sleep is likely crucial for recovery in COVID-19 survivors. 11 Sleep issues might worsen the adverse effects of COVID-19 on both physical and mental well-being.…”
Section: Introductionmentioning
confidence: 99%